2019
DOI: 10.1055/s-0039-1686963
|View full text |Cite
|
Sign up to set email alerts
|

Helmet Use among Two Wheeler Female Riders

Abstract: Introduction The frequency of traffic collisions in India is among the highest in the world with more than 135,000 traffic collision-related deaths occurring every year. The “Global Status Report on Road Safety” listed by the World Health Organization identified the major causes of injury as driving over the speed limit, driving under the influence, and not using helmets and seat belts. Women face unique challenges after traumatic brain injury, due to differential laws and their enforcement. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Severe head injury continues to be a nightmare due to the associated high mortality and morbidity, and contributes immensely to socioeconomic losses in India and other developing countries. [10][11][12] SHI increases the body's metabolic responses, and therefore nutritional demands, similar to subarachnoid hemorrhage. [13][14][15] Fasting along with hypermetabolism increases the rate of gluconeogenesis resulting in mobilization of amino acids initially from skeletal muscles and later from other visceral organs, which in turn leads to severe wasting of the lean body mass, impairment of vital organ function, and diminution in reparative and immune process.…”
Section: Discussionmentioning
confidence: 99%
“…Severe head injury continues to be a nightmare due to the associated high mortality and morbidity, and contributes immensely to socioeconomic losses in India and other developing countries. [10][11][12] SHI increases the body's metabolic responses, and therefore nutritional demands, similar to subarachnoid hemorrhage. [13][14][15] Fasting along with hypermetabolism increases the rate of gluconeogenesis resulting in mobilization of amino acids initially from skeletal muscles and later from other visceral organs, which in turn leads to severe wasting of the lean body mass, impairment of vital organ function, and diminution in reparative and immune process.…”
Section: Discussionmentioning
confidence: 99%
“…Jinnah came across a surprising finding that older girls were less likely to wear protective gear when compared to boys despite being the less affected gender in other age-groups [106]. Girls and women were found to be less willing to use helmets than bikers and two-wheelers [107][108][109].…”
Section: Indirect Risk Factors-helmet Usementioning
confidence: 99%
“…Stricter enforcement of helmet law is needed, as education and knowledge per se may not instill helmet use. 10…”
Section: Review Of Literaturementioning
confidence: 99%
“…Stricter enforcement of helmet law is needed, as education and knowledge per se may not instill helmet use. 10 Hofmann et al conducted a study on fact and fiction regarding motorcycle helmet use, associated injuries, and related costs in the United States. It was concluded that North American trauma surgeons wear helmets when they ride motorcycles and believe that these devices are highly protective, leading to a reduction in brain injury and subsequent health care costs.…”
Section: Review Of Literaturementioning
confidence: 99%